Dynamic succession of microbial compost communities and functions during Pleurotus ostreatus mushroom cropping on a short composting substrate - Liu, Qin; Kong, Weili; Cui, Xiao; Hu, Sujuan; Shi, Ziwen; Wu, Jie; Zhang, Yuting; Qiu, Liyou (Frontiers in Microbiology, 2022)
Cultivating Pleurotus ostreatus, a typical primary decomposer of lignocellulose, on a short composting substrate is novel procedure. However, the microbiome and microbial metabolic functions in the composting substrate during the mushroom cropping is unknown. Results showed that the hemicellulose, cellulose and lignin in the short composting substrate were decomposed of 42.76%, 34.01% and 30.18%, respectively, during the oyster mushroom cropping process. In addition, the contents of hemicellulose, cellulose and lignin in the composting substrate were reduced rapidly and negatively correlated with the abundance of the Actinobacteria phylum. The activities of protease, laccase and cellulase fastly increased in the period of before oyster mushroom spawning to full colonization and were positively correlated to the abundance of Actinobacteria phylum. The total abundance of bacteria domain gradually decreased by only approximately 15%, while the abundance of Actinobacteria phylum increased by 68% and was positively correlated with that of oyster mushroom. The abundance of oyster mushroom increased by 50 times from spawning to first flush fructification. The dominant genera, all in the order of Actinomycetales, were Cellulosimicrobium, Mycobacterium, Streptomyces and Saccharomonospora. The total abundance of genes with functions annotated in the Clusters of Orthologous Groups of proteins (COG) for Bacteria and Archaea and Kyoto Encyclopedia of Genes and Genomes (KEGG) database for all three life domains was positively correlated. The three metabolic pathways for carbohydrates, amino acids and energy were the primary enrichment pathways in KEGG pathway, accounting for more than 30% of all pathways, during the mushroom cropping in which the glycine metabolic pathway, carbon fixation pathways in prokaryotes and methane metabolism were all dominated by bacteria. The genes of cellulolytic enzymes, hemicellulolytic enzymes, laccase, chitinolytic enzymes, peptidoglycanlytic enzymes and ammonia assimilation enzymes with abundances from 0.28% to 0.24%, 0.05% to 0.02%, 0.02% to 0.01%, 0.14% to 0.08%, 0.39% to 0.16% and 0.13% to 0.12% during the mushroom cropping identified in the Evolutionary Genealogy of Genes: Non-supervised Orthologous Groups (eggNOG) database for all three life domains were all aligned to COG database. The relationship between oyster mushrooms and bacteria was cooperative, Actinomycetales were oyster mushroom growth promoting bacteria.